2015
DOI: 10.1007/s11033-015-3861-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MMP-13 prevents diet-induced obesity in mice and suppresses adipogenesis in 3T3-L1 preadipocytes

Abstract: Adipose tissue remodeling by the matrix metalloproteases (MMPs) is critical for tissue hypertrophy and obesity. MMP-13 is an important protein that is highly expressed in adipose tissue but whose potential role in adipose tissue expansion is poorly characterized. We investigated the effect of pharmacological inhibition of MMP-13 with a selective inhibitor, CP-544439, on adipose tissue mass in mice on a high fat diet, and determined the effect of the inhibitor during in vitro adipocyte differentiation of 3T3-L1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Our previous studies using synovial fibroblasts and intervertebral disc (IVD) cells have identified MMPs to be strongly upregulated in response to HTRA1 stimulation, being mediated through the production of reactive fibronectin species . In addition to their ability to induce HSPG cleavage and shedding , MMPs are also potent regulators of adipogenesis, having both inhibitory and stimulatory effects . This led us to investigate the possibility that MMP production by hMSCs undergoing adipogenesis might be regulated by HTRA1.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies using synovial fibroblasts and intervertebral disc (IVD) cells have identified MMPs to be strongly upregulated in response to HTRA1 stimulation, being mediated through the production of reactive fibronectin species . In addition to their ability to induce HSPG cleavage and shedding , MMPs are also potent regulators of adipogenesis, having both inhibitory and stimulatory effects . This led us to investigate the possibility that MMP production by hMSCs undergoing adipogenesis might be regulated by HTRA1.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of MMP-9 in this study was upregulated in the first 2 days of stimulation for adipogenic differentiation, followed by a rapid decrease until the end of differentiation, suggesting that the upregulation of MMP-9 does not necessarily have a key role in this process [14]. In another study, treating preadipocytes with a selective inhibitor for MMP-13 or silencing MMP-13 by siRNA resulted in reduced adipogenic differentiation, suggesting the important role of MMP-13 in adipogenesis [15]. …”
Section: Role Of Mmps In the Differentiation Of Mscsmentioning
confidence: 97%
“…Bauters et al (2015), in fact, observed that murine embryonic fibroblasts derived from MMP-2 deficient mice and MMP-2 knockdown 3T3-F442A pre-adipocytes showed significantly impaired differentiation into mature adipocytes with 90% reduction of intracellular lipid content and expression of proadipogenic markers. In the same way, Shih and Ajuwon (2015) showed that MMP-13 knockdown 3T3-L1 cells display reduced differentiation and reduced expression of PPARg.…”
Section: Matrix-metalloproteinases: a Crucial Link Between Obesity Anmentioning
confidence: 78%